Treatment of Kinesiology Taping Combined with Exercise Training in Children with Foot Valgus Caused by Cerebral Palsy - Songyin ZHENG; Yan WANG; Dongliang XIANG; Yuntana WU; Haifeng YANG; Shuang LI; Yan WANG; Huijie CHEN (康复学报)
Objective:To investigate the clinical effect of kinesiology taping combined with exercise training in children with foot valgus caused by cerebral palsy.Methods:The children aged 2 to 6 years old with foot valgus caused by cerebral palsy who were treated in the rehabilitation center of the Second Affiliated Hospital of Heilongjiang University of Traditional Chinese Medicine from January 2018 to April 2019 were selected as the research subjects, and 60 cases met the inclusion criteria were selected and were divided into control group and treatment group according to the random number table method, with 30 cases in each group. The control group was given conventional treatment (exercise therapy, acupuncture treatment, massage therapy); the treatment group was given kinesiology taping on the basis of conventional treatment and the patch was removed after 24 hours, followed by another patch at an interval of 24 hours. Both groups were treated 12 weeks. Before and after treatment, the children in both groups were respectively evaluated by footprint map three-line method for foot valgus degree and relaxed calcaneal stance position (RCSP) angle measurement.Results:There was no significant difference between the two groups in terms of foot valgus degree and angle of RCSP before treatment (P>0.05). After 12 weeks'treatment, the foot valgus degree in the treatment group was improved, and the difference was statistically significant compared with before treatment (P<0.05). After treatment the foot valgus degree in the treatment group was better than that in the control group, and the difference was statistically significant (P<0.05). After treatment angle of RCSP in the control group was (-5.48±1.04) °, and angle of RCSP in the treatment group was (-4.83±0.32) °, which was statistically significant compared with before treatment in each group respectively (P<0.001), suggesting that angle of RCSP was improved in both groups. After treatment, the angle of RCSP in the treatment group better than that in the control group, the difference was statistically significant (P<0.01).Conclusion:Kinesiology taping combined with exercise training can effectively improve foot valgus caused by cerebral palsy in children.